Characterization of Dengue Virus NS4A and NS4B Protein Interaction - Zou, Jing (J Virol, 2015)
Flavivirus replication is mediated by a membrane-associated replication complex where viral membrane proteins NS2A, NS2B, NS4A, and NS4B serve as the scaffold for the replication complex formation. Here, we used dengue virus serotype 2 (DENV-2) as a model to characterize viral NS4A-NS4B interaction. NS4A interacts with NS4B in virus-infected cells and in cells transiently expressing NS4A and NS4B in the absence of other viral proteins. Recombinant NS4A and NS4B proteins directly bind to each other with an estimated K(d) (dissociation constant) of 50 nM. Amino acids 40 to 76 (spanning the first transmembrane domain, consisting of amino acids 50 to 73) of NS4A and amino acids 84 to 146 (also spanning the first transmembrane domain, consisting of amino acids 101 to 129) of NS4B are the determinants for NS4A-NS4B interaction. Nuclear magnetic resonance (NMR) analysis suggests that NS4A residues 17 to 80 form two amphipathic helices (helix α1, comprised of residues 17 to 32, and helix α2, comprised of residues 40 to 47) that associate with the cytosolic side of endoplasmic reticulum (ER) membrane and helix α3 (residues 52 to 75) that transverses the ER membrane. In addition, NMR analysis identified NS4A residues that may participate in the NS4A-NS4B interaction. Amino acid substitution of these NS4A residues exhibited distinct effects on viral replication. Three of the four NS4A mutations (L48A, T54A, and L60A) that affected the NS4A-NS4B interaction abolished or severely reduced viral replication; in contrast, two NS4A mutations (F71A and G75A) that did not affect NS4A-NS4B interaction had marginal effects on viral replication, demonstrating the biological relevance of the NS4A-NS4B interaction to DENV-2 replication. Taken together, the study has provided experimental evidence to argue that blocking the NS4A-NS4B interaction could be a potential antiviral approach. IMPORTANCE Flavivirus NS4A and NS4B proteins are essential components of the ER membrane-associated replication complex. The current study systematically characterizes the interaction between flavivirus NS4A and NS4B. Using DENV-2 as a model, we show that NS4A interacts with NS4B in virus-infected cells, in cells transiently expressing NS4A and NS4B proteins, or in vitro with recombinant NS4A and NS4B proteins. We mapped the minimal regions required for the NS4A-NS4B interaction to be amino acids 40 to 76 of NS4A and amino acids 84 to 146 of NS4B. NMR analysis revealed the secondary structure of amino acids 17 to 80 of NS4A and the NS4A amino acids that may participate in the NS4A-NS4B interaction. Functional analysis showed a correlation between viral replication and NS4A-NS4B interaction, demonstrating the biological importance of the NS4A-NS4B interaction. The study has advanced our knowledge of the molecular function of flavivirus NS4A and NS4B proteins. The results also suggest that inhibitors of the NS4A-NS4B interaction could be pursued for flavivirus antiviral development.